PRAKTIK SOSIAL KOMUNITAS PURWO AYU MARDI UTOMO DALAM PEMBANGUNAN DESA KESUGIHAN - Purwanty, Ike Dewi (Paradigma, 2021)
The stream of belief are still experiencing discrimination by the community. This is inversely proportional to what was experienced by the Purwo Ayu Mardi Utomo community, Kesugihan Village, which was able to contribute greatly to village development. This research reveals how the social practices of the Purwo Ayu community in village development by analyzing the habitus, capital and domains. This research is a qualitative research with the perspective of Pierre Bourdieu's theory of practice The results showed that the habitus community in development underwent a change from the old habitus to the new habitus. The old habit of the community is to always be useful to the community by helping to improve the welfare of the community in preserving the cultural heritage of their ancestors. This makes the 2 practice of social communities change from the construction of public facilities to cultural development in the form of Javanese language learning activities and musical exercises. The activity was held with the aim that Javanese cultural heritage is maintained and sustainable. The capital used in activities is economic capital in the form of the availability of places and facilities for activities. Social capital in the form of full support from the village government. Cultural capital in the form of knowledge about Javanese culture. Symbolic capital is the oldest belief system with the most followers in Ponorogo Regency. The area used is Kesugihan Village, Pulung District, Ponorogo Regency. The habits and capital owned by the Purwo Ayu community make the community maintain its existence. Keywords: Stream of Belief, Development, Social Practices